The Moderating Role of Top Management Commitment in the Relationship Between Auditor Competence, Professional Skepticism, Risk-Based Internal Audit, and Audit Quality - Siti Maleha; Lilis Ardini (Varied Knowledge Journal, 2026)
This study investigates and analyzes the effect of internal auditor competence, professional skepticism, and the implementation of Risk-Based Internal Audit   (RBIA) on the internal audit quality. Also it examines and analyzes the role of the top management commitment as a moderating variable. Furthermore, the study applies quantitatively, with explanatory approach. The data were collected using a purposive sampling. In line with that, 117 cross sector internal auditors in Indonesia were chosen as samples, based on inclusion criteria given. Moreover, a closed-questionnaire and a Likert scale were used to support the data collection. Moderated Regression Analysis (MRA) with SPSS was used to examine direct effect among variables. It was also implemented to investigate effect significance of moderation interaction statistically. As a result, the study shows that internal auditor competence, professional skepticism, and the implementation of RBIA have a positive and significant effect on the internal audit quality. Additionally, the moderation testing indicates that the top management commitment strengthens the effect of internal auditor competence as well as the implementation of RBIA. Unfortunately, it does not moderate professional skepticism. Therefore, the increase of internal audit quality forces the optimization of auditor capability and the  empowerment  of management support  structurally, including  sustainable consistency of audit recommendation within the organization.